Das estratégias globais ao formato local: o discurso publicitário adaptado às necessidades de cada público - Nascimento, Rodney de Souza (2011)
THE ADVERTISING CAMPAIGNS of global companies backfi re due to cultural barriers when they try to come across with the same message in different countries. The concern and respect with the name of the brands and the language used in some countries are mainly a result of the regional characteristics of such countries. Thus, to standardize the language worldwide is the great challenge for the large corporations and, mostly, for the advertising agencies. In many cases, the solution was to think globally and to act locally. In such a way, the companies, through its advertising agencies, had started to develop campaigns capable of interacting with this new order. The segment of credit cards has been especially capable of doing so. These companies had changed the concept of communication within their advertising campaigns, being not only a symbol of status, but also substituting the paper-currency and becoming the world-wide accepted plastic money. Thus, this research is a result of the need to understand how the advertising campaigns have conquered markets in similar ways by means of a global alignment of communication and standardized language in different markets. As this research main object is the globalized advertising discourse; the aim of this research is to understand the strategies used in the MasterCard credit card s Priceless campaign, which has been able to get a global alignment in order to pass its message though in a standardized way in many different cultures, even though it makes use of cultural specifi c values. In this research, using some background on culture and consumption theories, we analyze 8 advertisement pieces from the priceless credit card campaign, all published in the Brazilian printed media from 1998 through 2006